2021
DOI: 10.1002/csr.2131
|View full text |Cite
|
Sign up to set email alerts
|

The influence of green trust on travel agency intentions to promote low‐carbon tours for the purpose of sustainable development

Abstract: Through corporate social responsibility, tourism companies can contribute to sustainable development by embracing concepts such as low-carbon tourism and environmental protection. The purpose of this research was to determine the intention of Taiwanese travel agencies to promote low-carbon tours by incorporating government-approved eco-friendly travel products. In total, 427 valid questionnaires were collected and examined by means of PLS-SEM. The findings showed that green trust not only had a significant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 92 publications
2
19
1
Order By: Relevance
“…On the other hand, some researchers studied on the starring role of green trust in constructing green brands (Butt et al, 2017;Chen, 2010). A recent study (Sung et al, 2021) also worked on the link between green trust and the theory of planned behavior (TPB) to show how green trust influences customers' willingness in determining green hotels visit intentions. But not much study are found that considered customers' knowledge and concern about environment and how they are linked with their green trust in choosing green hotels to stay or visit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some researchers studied on the starring role of green trust in constructing green brands (Butt et al, 2017;Chen, 2010). A recent study (Sung et al, 2021) also worked on the link between green trust and the theory of planned behavior (TPB) to show how green trust influences customers' willingness in determining green hotels visit intentions. But not much study are found that considered customers' knowledge and concern about environment and how they are linked with their green trust in choosing green hotels to stay or visit.…”
Section: Introductionmentioning
confidence: 99%
“…, 2017; Chen, 2010). A recent study (Sung et al. , 2021) also worked on the link between green trust and the theory of planned behavior (TPB) to show how green trust influences customers' willingness in determining green hotels visit intentions.…”
Section: Introductionmentioning
confidence: 99%
“…In the sustainable literature, this statement of GHA disinformation is known as greenwashing, which has been shown to reduce TGH [16]. Therefore, it is important to provide GHA information transparently and correctly to create a good relationship between green hotels and TGH [32]. Previous studied on 521 respondents using a two-stage survey found that trust toward green hotels had a positive effect on behavioral intention to stay at green hotels [28].…”
Section: Trust Toward Green Hotelsmentioning
confidence: 99%
“…Results for the indirect effects are presented in Table 7. Additionally, we calculated the values for VAF (Variance Accounted For), which were determined using the following formula: 'VAF stands for indirect effects/total effects' [90]. Considering the result for the total effect of 0.377, the VAF value was 0.263 (26.3%) (Table 7).…”
Section: Mediation Analysismentioning
confidence: 99%
“…Considering the result for the total effect of 0.377, the VAF value was 0.263 (26.3%) (Table 7). According to Hair et al [91] and Sung et al [90], partial mediation occurs when the VAF is between 20% and 80%. Thus, this aspect consolidated our previous result of partial mediation, confirming our initial Hypothesis 7.…”
Section: Mediation Analysismentioning
confidence: 99%